THE RELATIONSHIP BETWEEN RESPONSE TIME AND SERVICE QUALITY AT THE EMERGENCY DEPARTMENT OF LABUANG BAJI HOSPITAL, MAKASSAR - Sintia M. Rahmola; Habibi; Evi Sri Dahrianti (CV. Adiba Aisha Amira, 2026)
Background: Fast and appropriate service in the Emergency Department (ED) is a primary determinant of patient safety and hospital service quality. Delays in medical personnel's response time can have fatal consequences on a patient's clinical condition and reduce public trust in the quality of healthcare. Objective: This study aims to analyze the relationship between response time and service quality in the ED of Labuang Baji Hospital, Makassar City, in 2026. Methods: This type of research is quantitative with a cross-sectional design. The research sample consisted of 83 respondents selected using the accidental sampling technique. Research instruments included observation sheets to measure response time and questionnaires to assess service quality. Data were statistically analyzed using the Chi-Square test (α=0.05). Results: The results showed that the majority of respondents received response times in the fast category (71.1%) and rated service quality in the good category (62.7%). Bivariate analysis showed a significant relationship between response time and service quality with a p-value = 0.000 (p<0.05). Conclusion: There is a significant relationship between nurse response time and service quality in the ED of Labuang Baji Hospital. The faster the response time provided by medical personnel, the higher the patient's perception of the quality of service received.